Bioinformatics in Sustainable Healthcare and Energy Efficiency - Saif Saad Ahmed; Sumaia Ali Alal; Mina Louay Badran; Samer Saeed Issa; Ghada S. Mohammed; M. Batumalay (International Journal of Engineering, Science and Information Technology, 2025)
While originating in genomics, bioinformatics is emerging as a powerful tool for optimizing complex, energy-intensive systems. This paper investigates a novel application of bioinformatics across four critical sectors—healthcare, biofuel production, renewable energy, and the Internet of Things (IoT)—to enhance energy efficiency, operational reliability, and system adaptability. Using a mixed-methods approach that combines statistical modeling, algorithm development, and institutional case studies, this research quantifies the impact of bioinformatics-driven interventions on key performance and energy metrics. The results demonstrate significant and consistent improvements across all domains. In healthcare, integrating genomic analytics and adaptive controls led to energy savings of up to 12.8%. For biofuel production, bio-inspired enzymatic and microbial process optimization reduced energy intensity by as much as 18.1% per liter. In the renewable energy sector, bioinformatics-based modeling increased the net efficiency of a solar farm by 50%. Furthermore, IoT systems with embedded bioinformatics algorithms achieved up to 15.8% improvement in energy-aware operations, confirming the methodology's cross-disciplinary value. This study positions bioinformatics not merely as a scientific tool but as a core organizing principle for fostering sustainability in digitized infrastructures. While challenges such as computational overhead and ethical governance remain, this research provides compelling evidence that bioinformatics can serve as a catalyst for cross-industrial environmental innovation. Future work should focus on integration with high-performance computing and the development of socio-ethical frameworks to ensure scalable and responsible deployment for energy efficiency.